Histone Variant H2A.Z Is Required for the Maintenance of Smooth Muscle Cell Identity as Revealed by Single-Cell Transcriptomics. Issue 20 (13th November 2018) - Yao, Fang; Yu, Peng; Li, Yue; Yuan, Xinli; Li, Zheng; Zhang, Tao; Liu, Fei; Wang, Yingbao; Wang, Yin; Li, Dandan; Ma, Baihui; Shu, Chang; et al.
Abstract : Background: Histone variants endow chromatin with specific structures, and play essential roles in development and diseases. However, little is known about their roles in controlling cell identity in vascular diseases. Methods: Given the cell heterogeneity in atherosclerotic lesions, we applied single-cell RNA-Sequencing to analyze diseased human arteries, and identified histone variant H2A.Z as a key histone signature to maintain vascular smooth muscle cell (VSMC) identity. Results: We show that H2A.Z occupies genomic regions near VSMC marker genes, and its occupancy is decreased in VSMCs undergoing dedifferentiation. Mechanistically, H2A.Z occupancy preferentially promotes nucleosome turnover, and facilitates the recruitment of SMAD3 and MED1, thereby activating VSMC marker gene expression. In addition, H2A.Z expression is dramatically reduced at both mRNA and protein levels in diseased human vascular tissues compared to those in normal arteries. Notably, in vivo overexpression of H2A.Z rescues injury-induced loss of VSMC identity and neointima formation. Conclusions: Together, our data introduce dynamic occupancy of a histone variant as a novel regulatory basis contributing to cell fate decisions, and imply H2A.Z as a potential intervention node for vascular diseases. Abstract : Supplemental Digital Content is available in the text.